IMPLEMENTASI PASAL 74 UNDANG-UNDANG NO. 40 TAHUN 2007 TENTANG PERSEROAN TERBATAS MENGENAI TANGGUNG JAWAB SOSIAL PERUSAHAAN DI PTPN III - Delfani Febryana Lubis; Bismar Nasution; Sunarmi Sunarmi; Mahmul Siregar (Universitas Sumatera Utara, 2017)
ABSTRACT The Implementation of Corporate Social Responsibility or Corporate Social Responsibility (CSR) by PTPN III conducted based on Article 88 of Law No. 19 of 2003 on State Enterprises (BUMN Law) and Article 74 of Law No. 40 Year 2007 regarding Limited Liability Company (Company Law) but the implementation of CSR can not be implemented by the Company Law and channeled properly because the Company Law does not expressly regulate the implementation of CSR, causing an unstable state in its implementation. Based on the background problems above it is found that First, the rule of law in the Corporate Social Responsibility before and after the enactment of Article 74 of Company Law, Second, The Implementation of Corporate Social Responsibility by PTPN III based on Article 74 of Company Law, Third, stakeholders participation in The implementation of The Obligations Social responsibility in PTPN III.Keywords : Corporate, BUMN, Implementation, Social Responsibility